SMEs, electronically-mediated working and data security: Cause for concern? - Fintan Clear (International Journal of Business Science & Applied Management (IJBSAM), 2007)
Security of data is critical to the operations of firms. Without the ability to store, process and transmit data securely, operations may be compromised, with the potential for serious consequences to trading integrity. Thus the role that electronically-mediated working plays in business today and its dependency on data security is of critical interest, especially in light of the fact that much of this communication is based on the use of open networks (i.e. the Internet). This paper discusses findings from a "WestFocus" survey on electronically-mediated working and telework amongst a sample of SMEs located in West London and adjacent counties in South-Eastern England in order to highlight the problems that such practice raises in terms of data security. Data collection involved a telephone survey undertaken in early 2006 of 378 firms classified into four industrial sectors ("Media", "Logistics", "Internet Services" and "Food Processing"). After establishing how ICTs and the Internet are being exploited as business applications for small firms, data security practice is explored on the basis of sector and size with a focus on telework. The paper goes on to highlight areas of concern in terms of data security policy and training practice. Findings show some sector and size influences.
Keywords: 650; data security; small firms; ICT adoption behaviour; electronically-mediated working; telework; security policy; security training; sector; firm size